The RING finger- and PDZ domain-containing protein PDZRN3 controls localization of the Mg(2+) regulator claudin-16 in renal tube epithelial cells - Marunaka, Kana (J Biol Chem, 2017)
Ion exchange in the renal tubules is fundamental to the maintenance of physiological ion levels. Claudin-16 (CLDN16) regulates the paracellular reabsorption of Mg(2+) in the thick ascending limb of Henle's loop in the kidney, with dephosphorylation of CLDN16 increasing its intracellular distribution and decreasing paracellular Mg(2+) permeability. CLDN16 is located in the tight junctions, but the mechanism regulating its localization is unclear. Using yeast two-hybrid systems, we found that CLDN16 binds to PDZRN3, a protein containing both RING-finger and PDZ domains. We also observed that the carboxyl terminus of the cytoplasmic CLDN16 region was required for PDZRN3 binding. PZDRN3 was mainly distributed in the cytosol of rat kidney cells and upon cell treatment with the protein kinase A inhibitor H-89, colocalized with CLDN16. H-89 also increased mono-ubiquitination and the association of CLDN16 with PDZRN3. Mono-ubiquitination levels of a K275A mutant were lower, and its association with PDZRN3 was reduced compared with wild-type (WT) CLDN16 and a K261A mutant, indicating that Lys-275 is the major ubiquitination site. An S217A mutant, a dephosphorylated form of CLDN16, localized to the cytosol along with PDZRN3 and the endosomal marker Rab7. PDZRN3 siRNA increased cell-surface localization of WT CLDN16 in H-89-treated cells or containing the S217A mutant and also suppressed CLDN16 endocytosis. Of note, H-89 decreased paracellular Mg(2+) flux in WT CLDN16 cells, and PDZRN3 siRNA increased Mg(2+) flux in the H-89-treated WT CLDN16 and S217A mutant cells. These results suggest that PDZRN3 mediates endocytosis of dephosphorylated CLDN16 and represents an important component of the CLDN16-trafficking machinery in the kidney.